The Influence Of Double-Date Promotions And Cash On Delivery On Purchase Decisions Through Purchase Intention Among Shopee Users In Jambi City - Depi Susanti; Rofiqoh Ferawati; Muthmainnah (International Journal of Management and Business Economics, 2026)
This study aims to analyze the effect of double date promotions and Cash on Delivery (COD) on purchase decisions, with purchase intention as a mediating variable among Shopee users in Jambi City. This study employed an associative quantitative approach using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method with SmartPLS 4. The population consisted of millennial Muslim women aged 30–44 years residing in Jambi City who had purchased fashion products through Shopee. A sample of 100 respondents was selected using purposive sampling. The findings indicate that double date promotions have a positive and significant effect on purchase intention, while purchase intention significantly influences purchase decisions. Furthermore, purchase intention fully mediates the relationship between double date promotions and purchase decisions. In contrast, COD does not significantly affect either purchase intention or purchase decisions, and purchase intention does not mediate the relationship between COD and purchase decisions. These results suggest that consumers do not make purchasing decisions directly because of promotional programs; rather, promotions first increase purchase intention, which subsequently drives purchasing decisions. This study highlights the crucial role of purchase intention as a mechanism through which promotional strategies influence consumer behavior. Practically, the findings imply that Shopee sellers and digital marketers targeting millennial Muslim women should prioritize attractive and well-designed double date promotional campaigns to strengthen consumers’ purchase intention, rather than relying solely on COD facilities to encourage purchasing decisions.